Análise comparativa de pesquisadores considerando características de múltiplas áreas de pesquisa - Harlley Augusto de Lima (2014)
The impact of scientific research has traditionally been quantified using productivity indices such as the well-known h-index. On the other hand, different research fields and even different research areas within a single field may have different publishing patterns, which may not be well described by a single, global index. In this work, we argue that productivity indices should account for the singularities of the publication patterns of different research areas, in order to produce an unbiased assessment of the impact of scientific research. Inspired by ranking aggregation approaches in distributed information retrieval, we propose a novel approach for ranking researchers across multiple research areas. Our approach is generic and produces cross-area versions of any global productivity index, such as the volume of publications, citation count and even the h-index. Our thorough evaluation considering multiple areas within the broad field of Computer Science shows that our cross-area indices outperform their global counterparts when assessed against the official ranking produced by the official Brazilian agency. As a result, this thesis contributes a valuable mechanism to support the decisions of funding and research agencies, for example, in any research assessment effort.